SISTEM PAKAR EVALUASI PSIKOLOGIS REMAJA PADA LEMBAGA INDONESIA CREATIVE CENTRE JAKARTA - Henny Destiana; Sari Suleha (LPPM Universitas Bina Sarana Informatika, 2016)
Expert System or popular name is psikotest surely already in common and become a regular activity in schools and institutions both large companies and small companies. There are various types of offers and the quality offered, but generally give the same picture as good.Psychological evaluations for students is a device used to illustrate the uniqueness of the individual's personality and their potential. Based on the understanding of the needs from the school, obtained from research on existing educational institutions that schools have needs different levels.The answer from an expert on a consultation of trustworthy and accountable and has a value of quality results, because an expert control field has been practiced based on the experience and knowledge gained. The method used in the design of this expert system application is Ranut Forward. Application of expert system is useful to help users in analyzing interest talents by way of input answers of statements that have been there on this expert system in every aspect from the input data condition statement to answer her, then get the results of the analysis of interest flair complete with analysis profession that should be focused over the interests of his talent. Key Word : Psychological Evaluation, Expert System, Interest Talents